Wearing ballistic and weighted vests increases front kick forces - Vagner, M.; Thiel, D.; Jelen, K..; Tomsovsky, L.; Kubovy, P.; Tufano, J. J (Archives of Budo, 2018)
Background and Study Aim: Front kicks are often used in hand-to-hand military combat training. To mimic real-life combative environments, personal protective equipment (PPE) that includes a ballistic vest should be worn during training. The aim of this study was the effects of ballistic and weighted vests on front kick kinetics.